Sosialisasi Manfaat Media Sosial Untuk Meningkatkan Promosi Bisnis Di Leter U Desa Sido Luhur - Irawan, Sella Devi; Anggriani, Ida; Suwarni, Suwarni; Wagini, Wagini (Universitas Dehasen Bengkulu, 2023)
The development of today's technological era is increasing, the number of people who have followed technological developments is used in many ways and has advantages that can be obtained from technology users, who make use of social media easily among the public, especially in Sidoluhur village, Sukaraja sub-district, for example carrying out promotions which can be done online. The purpose of carrying out community service activities is to help the community recognize and understand the benefits of social media in increasing business promotion using social media, activities carried out in the form of community service carry out socialization methods to residents and youth circles in Sido sublime village, Sukaraja sub-district, results of community service In this community, I do socialization, namely explaining the benefits of social media which can broaden the introduction of products that are carried out by uploading a product on social media such as Instagram, Facebook, and WhatsApp. Social media is indeed very useful for those who carry out a promotion in the business they founded. , then local residents can take advantage of social media with various features available in social media to carry out promotional activities in doing business.